Sexuality and Mental Health of Pakistani-Descent Adolescent Girls living in Canada: Perceptions and Recommendations - Neelam Saleem Punjani; Elizabeth Papathanassoglou; Kathy Hegadoren; Saima Hirani; Zubia Mumtaz; Margot Jackson (MDPI AG, 2023)
In Canada, the demands of female immigrant adolescents in terms of sexual health are largely unmet and have grown significantly in recent years. According to studies, racialized immigrant adolescents are less likely than non-immigrant adolescents to be knowledgeable about sexual and reproductive health and to use resources for sex education and related services. This difference seems to be related to socio-cultural and religious practices in Pakistani immigrant adolescents. This paper intends to explain the viewpoints of female adolescents of first- or second-generation Pakistani descent who reside in Canada with regard to their development of sexuality and psychological well-being. Moreover, this paper also describes how female adolescents perceive the necessity to support their sexuality as they go through the adolescent stage. Individual interviews and timelines were created using qualitative interpretative descriptive design. We included 21 female adolescents of first- or second-generation Pakistani ethnicity using a purposive sample. Data analysis was performed using a thematic analysis. The findings indicate that immigrant adolescent girls received conflicting messages about sexuality from their parents which impacted their psychological well-being. Additionally, survey participants noted that prejudice, exclusion from sex education classes, and a lack of sexual health information contributed to social isolation, health care avoidance, and poor mental health outcomes like melancholy and anxiety among adolescent girls. The absence of sexuality-related communication with parents and the scarcity of medical professionals who can relate to and address the needs and realities of immigrants may have an impact on the participants' experiences. Female immigrant girls also spoke up on the need for open, honest, and stigma-free conversations as well as for the need to end the taboo around the subject of sexuality. This study used principles from both intersectionality and postmodern feminist theories to increase our understanding of the interplay between the experiences of developing sexuality and overall well-being in female immigrant adolescents of Pakistani descent. It is crucial to involve, listen to, and incorporate female adolescents' voices when planning and implementing interventions to support healthy sexuality among immigrant adolescents.